Review: Cost Effectiveness Analysis And Its Implementation Regarding Hypertension Treatment - Dini Nabilah; Santi Purna Sari; Marlina Dewiastuti (Green Publisher Indonesia, 2024)
Healthcare financing involves the management of various efforts to mobilize, allocate, and spend health funds to ensure the implementation of health development aimed at achieving the highest possible level of public health. Hypertension, a non-communicable disease (NCD) continues to evolve and poses a serious public health issue and leads to an increasing health financing burden. Health Social Security Agency (BPJS) indicated direct medical costs of hypertension IDR 3 trillion in 2017 and 2018. The variety of first-line antihypertensive combinations due to the numerous recommended first-line antihypertensive combinations in various guidelines highlights the importance of pharmacoeconomic studies to determine the most cost-effective combination. This review article aims to further discuss the implementation of the CEA method as a basis for treatment selection or decision-making regarding hypertension treatment. The nifedipine 60 mg and candesartan 32 mg combination is deemed the best, achieving a blood pressure reduction of 23,8/16,5 mmHg (p<0,01) compared to placebo and monotherapy reductions of 5,3/6,7 mmHg. Additionally, the nifedipine GITS - candesartan combination reduces vasodilator side effects incidence to 18,3% compared to 23,6% for nifedipine monotherapy, including a lower incidence of headaches (5,5% vs. 11%).